Ketika Satu Scan Menggantikan Uang Tunai: Pengalaman Pengguna terhadap QRIS sebagai Inovasi Layanan Perbankan Digital (Studi Kasus pada Subjek IN-01 dan Subjek IN-02) - Harun Aminuddin; Fika Syanty Ayu Febriella; Salwa Najiba; Ida Ayu Nuh Kartini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study examines user experiences in adopting QRIS (Quick Response Code Indonesian Standard) as a digital banking service innovation in Indonesia. Employing a descriptive qualitative approach with a case study method, the research involved two informants (IN-01 and IN-02) who were interviewed in-depth using a 15-item semi-structured interview guide. Thematic analysis identified five main themes: (1) situational-triggered QRIS adoption, (2) radical shift from cash to smartphone-based payments, (3) functional value through practicality and financial control, (4) dependence on digital infrastructure and emotional responses to system failures, and (5) positive perceptions of QRIS security and future prospects. The core finding reveals that QRIS has transformed from merely a payment alternative into a primary transactional instrument embedded in users' daily lives, positioning the smartphone as a digital wallet replacing cash both functionally and psychologically. This research contributes to the understanding of cashless society behavior among young Indonesian users, though findings are limited to the context of the two informants studied and are not intended for broad generalization.